Compendium of classification opinions : harmonized commodity description and coding system (World Customs Organization BrusselsBE, 2017)
Consists of a list, set out in the order of the headings and subheadings of the Harmonized Description and Coding System of the classification opinions adopted by the Customs Co-operation Council.
Keywords: TARIFFS